Get organized or perish: attracting FDI to grow small food enterprises in Bangladesh. Issue 3 (2nd September 2019) - Islam, Kamrul; Chitakunye, David
ABSTRACT: This study contributes to the literature surrounding sustainable business models for SMEs. Through the lens of the relationship between FDI, economic growth and labour force among small food enterprises in Bangladesh, we develop some propositions that can help SMEs to be more sustainable. We demonstrate how traditional business models need to reflect changing global contexts of SMEs. Whilst the pecking order theory suggests that SME owners must use internal sources of finance before external sources, we find that external financing is a significant factor for the growth of SMEs. Our findings contribute to an understanding of how SME managers can use FDI as a resource to develop growth strategies. This presents an opportunity for small food enterprises in Bangladesh to be more organized. Given that SMEs are often informationally opaque, getting organized will help them to become less informationally opaque, as well as reduce the finance gap by attracting FDI.